Characteristics of the Outdoor Environment Affording Physical Activity, Motor Competence, and Social Interactions in Children Aged 3–7 Years: A Systematic Review - Nicola Taylor; Andy Pringle; Clare M. P. Roscoe (Children, 2024)
Early childhood education (ECE) settings play a crucial role in promoting physical and social development among children aged 3–7 years. This systematic review sought to examine the associations between characteristics of ECE outdoor environments, social interactions, physical activity, and motor competence. The secondary aim examines previously applied methods to capture children’s behaviour in the context of their social and physical environment. Methods: This review used the PRISMA framework and study quality was assessed using the mixed-methods appraisal tool (MMAT). Keyword searches were conducted in seven databases. Studies were eligible if children were aged 3–7 years in ECE; physical activity, social interactions and/or motor competence were measured; location and/or social context were measured. Results were synthesised using an effect direct plot, a table of associations, and narrative synthesis. Results: Twenty-three studies from eight countries met the inclusion criteria. Intervention and controlled cross-sectional studies (n = 9) favoured high-quality outdoor environments rich in affordances, portable play equipment, and natural features to increase children’s physical activity, social interactions, and cooperative play. Cross-sectional and descriptive studies (n = 14) positively associated open grassy space, portable and fixed equipment, wheeled toys, and paths with physical activity (p < 0.05). Based on limited evidence, playground size and active games in small groups were associated with greater MC. Conclusions: The findings highlight the benefit of creating diverse affordance rich outdoor environments in early childhood settings to promote physical and social development. Limitations include variability in study designs and protocols for conducting systematic observations, thus emphasising the need for standardised approaches to future research.